Enzymes of Ammonia Assimilation in Fungi: An Overview - Pradeep V. Khajure, Rajkumar S. Meti, Shardor Ambarish, (Recent Research in Science and Technology, 2011)
Nitrogen is a major element found in many of the simple compounds and nearly all of the complex macromolecules of living cells. Nitrogen can be obtained either from organic source or inorganic source but ultimately it is converted into ammonia and glutamate. Ammonia is the preferredÃ‚Â Ã‚Â source of nitrogen. The assimilation of ammonia into glutamate and glutamine plays a central role in the nitrogen metabolism of all organisms. Glutamate dehydrogenase (GDH), Glutamate synthase (GOGAT), and glutamine synthetase (GS) are the key enzymes involved in ammonia assimilation. The specific steps in these pathways vary with the organism, but in virtually all cells glutamate (85%) and glutamine (15%) serve as the nitrogen donors for biosynthetic reactions. In fungi lot of work has been carried out on these enzymes from lower fungi to the higher ones and there are differences in the role played by theses enzymes. Thus knowledge of the formation of glutamate and glutamine from various nitrogen sources is crucial to our understanding of cell growth.Ã‚Â In this review an overall view of the elements present in ammonia assimilation especially in fungi will be carried out along with recent developments and concepts.